Information Processing And Cognitive Theories Of Learning - Brayadi, Brayadi; Supriadi, Supriadi; Manora, Hecksa (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
Gagne suggests in his theory that cognitive learning outcomes are the result of this learning pattern, namely intelligence which includes oral and written skills, the ability or capacity of each individual, long-term planning that has goals, and motor skills. Learning theories are learning theories that we can take from anywhere that is owned by cognitive learning experts, namely the thoughts of experts, habits, empirical research and the theory of learning itself. Cognitive learning is learning that refers to activities or activities that include various activities related to the learning process and information development to increase the quality according to the capacity of students through this method can improve the learning process of students who focus on the process of cognitive learning models.